Latero‐Oblique Radiography as a Diagnostic Tool for Equine Cervical Osteoarthritis. (September 2014) - Tambaschi, M.; Dunkel, B.; Mullard, J.; Wood, R.; Piercy, R.J.; Weller, R.
Abstract : Reasons for performing study: Equine cervical osteoarthritis is a common disease known to contribute to both neck pain and cervical vertebral compressive myelopathy. There are no published studies demonstrating the usefulness of latero‐oblique radiography as a diagnostic tool for cervical osteoarthritis. Objectives: To determine the sensitivity, specificity and positive and negative predictive values of latero‐oblique radiography as a diagnostic tool for cervical articular process joint osteoarthritis. Study design: Prospective cadaver study. Methods: Latero‐oblique radiographs and CT images were collected, and post mortem examinations performed, on 27 cadaver necks from Thoroughbred‐type horses of various ages and sexes. Two equine clinicians independently reviewed each set of images for the presence of osteoarthritis. The authors, under the guidance of a veterinary pathologist, reviewed all articular process joints for bony changes indicative of osteoarthritis. Results: The prevalence of osteoarthritis identified on CT images was 57.9% (Assessor A) and 23% (Assessor B). The prevalence of lesions identified on post mortem examination was 25.6%. Latero‐oblique radiography showed a low sensitivity for identifying osteoarthritis when compared to both CT imaging (6.3–16.1%) and post mortem examination (2.2–4.4%). However, it showed a high specificity when compared to both CT imaging (92.1–97.8%) and post mortem examination (87.2–95.0%). The positive predictive value for identifying osteoarthritis was moderate (40.9–80.0%) when compared to CT imaging and poor (4.2–18.2%) when compared to post mortem examination. The negative predictive value was moderate when compared to both CT imaging (42.9–76.3%) and post mortem examination (78.0–79.8%). Conclusions: Latero‐oblique radiography has low sensitivity, but high specificity for the detection of cervical osteoarthritis when compared to both CT imaging and post mortem examination. Further investigation comparing the sensitivity, specificity and positive and negative predictive values of latero‐oblique radiography vs. laterolateral radiography would determine whether taking latero‐oblique radiographs, which can be more difficult to obtain and interpret, is necessary for the diagnosis of cervical osteoarthritis in practice. Ethical animal research:  Ethical committee oversight not currently required by this congress: The study was performed on material obtained from an abattoir.Sources of funding:  None.Competing interests:  None.